Invasive plants facilitated by socioeconomic change harbor vectors of scrub typhus and spotted fever. - Chen-Yu Wei; Jen-Kai Wang; Han-Chun Shih; Hsi-Chieh Wang; Chi-Chien Kuo (Public Library of Science (PLoS), 2020)
BACKGROUND:Ecological determinants of most emerging vector-borne diseases are understudied, particularly for neglected tropical disease. Moreover, although socioeconomic impacts can have significant downstream effects on human risks to vector-borne diseases via a change in land cover, particularly facilitating the invasion of exotic plants, related studies remains very scarce. Scrub typhus and spotted fever are neglected diseases emerging around the globe and are transmitted by chigger mites and ticks infective of Orientia tsutsugamushi and Rickettsia spp., respectively, with small mammals as the primary hosts of both vectors. METHODOLOGY/PRINCIPAL FINDINGS:We investigated how invasions of the plant Leucaena leucocephala caused by widespread abandonment of farmlands driven by industrialization affected abundance of chiggers and ticks in Penghu Island, Taiwan. We determined ectoparasite abundance by trapping small mammals in three types of habitats (invasion site, agricultural field, human residential) every two months for a year. Based on ectoparasite burdens, invasion sites harbored more chiggers and ticks than the other two habitats. Furthermore, hosts maintained higher burdens of both vectors in early winter and burdens of chiggers were more stable across seasons in invasion sites, suggesting that sites with invasive plants could be a temporary refuge for both vectors and might help mitigate the negative influence of unfavorable climate. Infective rates of O. tsutsugamushi in chiggers and Rickettsia in ticks were also consistently not lower in invasion sites. Top soil temperature and relative humidity were similar across the three habitats, but invasion sites contained more of the rat Rattus losea, on which chiggers and ticks were more engorged than those from the most commonly trapped species (Suncus murinus shrew), indicating that abundance of the host R. losea instead of microclimate might better determine the abundance of both vectors. CONCLUSIONS/SIGNIFICANCE:This study highlights an important but largely neglected issue that socioeconomic change can have unexpected consequences for human health induced particularly by invasive plants, which could become a hotspot for emerging infectious diseases but usually are very hard to be eradicated. In the future, a more comprehensive approach that integrates socio-economics, land use, exotic species, and human health should be considered to fully understand potential emergence of vector-borne diseases.